Dominant Logic approach for health service information system: value creation and co-creation through asynchronous communication (RECIIS, 2013)
ABSTRACT This paper uses the approach known as Service Dominant Logic (SDL) and Co-creation of value to introduce the basic concepts of Service Science and SDL in the health information system area. Then the article shows that interaction through asynchronous communication may produce value. In this approach, one should not separate product attributes from service attributes, since they are complementary. Some Marketing concepts are present in our daily routine and can be applied to several service domains such as Education, Transport, Public Services, Health and Information and Communication Technology. Users of Health Systems have already been ranked in the context of Service Science. As part of an ongoing research that explores the use of virtual forums, the article presents an example - using the Forum DATASUS - to show the importance of interaction via asynchronous communication tool between users and service providers, in the development and implementation of Health Information Systems.Keywords: Services, ICT; Datasus; Forum; Health